2016
DOI: 10.1088/0029-5515/56/4/046011
|View full text |Cite
|
Sign up to set email alerts
|

First results of the use of a continuously flowing lithium limiter in high performance discharges in the EAST device

Abstract: As an alternative choice of solid plasma facing components (PFCs), flowing liquid lithium can serve as a limiter or divertor PFC and offers a self-healing surface with acceptable heat removal and good impurity control. Such a system could improve plasma performance, and therefore be attractive for future fusion devices. Recently, a continuously flowing liquid lithium (FLiLi) limiter has been successfully designed and tested in the EAST superconducting tokamak. A circulating lithium layer with a thickness of  &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…The CCD camera system is installed at the horizontal distance of R = 2.90 m, which is located at the toroidal angle ϕ = 270° as shown in figure 1. The CCD camera system viewing the opposite side of the LLL is a true color camera with 20 Hz frame [21], which can provide the distributions of edge plasma and impurity emissions as shown in the inset profile. The LiII (wavelength at 548.40 nm with green visible spectrum) emission distribution can be observed by the CCD camera system as shown in the inset figure.…”
Section: The Description Of the Emc3-eirene Codementioning
confidence: 99%
“…The CCD camera system is installed at the horizontal distance of R = 2.90 m, which is located at the toroidal angle ϕ = 270° as shown in figure 1. The CCD camera system viewing the opposite side of the LLL is a true color camera with 20 Hz frame [21], which can provide the distributions of edge plasma and impurity emissions as shown in the inset profile. The LiII (wavelength at 548.40 nm with green visible spectrum) emission distribution can be observed by the CCD camera system as shown in the inset figure.…”
Section: The Description Of the Emc3-eirene Codementioning
confidence: 99%
“…To date, most LM-PFC research efforts (CDX-U [8], FLiLi [9], etc) have operated with small amounts of lithium (~1-2 (kg)) so it is possible that even modest levels of impurity could cause noticeable changes to flow and massbalance of the lithium [8,9,68]. Reactor-scale systems will require drastically larger lithium inventories and flow rates of approximately 1.2 (kg s −1 ) per 1 (MWTh), as shown by equation (21) [18].…”
Section: Conservation Of Massmentioning
confidence: 99%
“…Furthermore, several experiments have already shown that using lithium-PFC's on portions of a tokamak interior can greatly improve plasma performance by reducing particle recycling, increasing energy confinement, and suppressing impurity emissions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in FTU, T-11M and CDX-U devices, plasma discharges with lower impurity control and higher confinement were achieved by using LLL [9][10][11][12][13][14]. Some promising results were also achieved in HT-7 and EAST by using a LLL [7,[15][16][17][18][19][20][21][22]. It was found that the H recycling was reduced by 20-30%, the particle confinement time increased by a factor of 2, the impurity emission intensity was decreased by about 10-20% and the energy confinement time was increased by 20%.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the corrosion behaviors of structural materials in liquid Li depend seriously on the experiment conditions. Several LLLs on HT-7 [16][17][18][19][20] and EAST [20][21][22] have been performed since 2009. Two kinds of static liquid lithium limiters with free surface and capillary-pore system (CPS) configuration were successively utilized in HT-7 in 2009 and 2011 with pressure less than 4×10 -5 Pa.…”
Section: Introductionmentioning
confidence: 99%